Implementing ECVET: crediting, recognition and transfer of learning outcomes between European target stipulations and national System conditions - Christiane Eberhardt (Bundesinstitut für Berufsbildung (BIBB), 2013)
In 2008 the European Parliament and Council passed the 'Recommendation on the establishment of a European Credit System for Vocational Education and Training (ECVET)'. The aim of ECVET is to facilitate the transfer and mutual recognition of learning outcomes attained in different education systems and in a variety of initial and advanced vocational training contexts. In past years a great number of steps have been undertaken at European level and in the Member States to create suitable framework conditions in which ECVET could be applied. In the present discussion paper, the question is raised as to how far ECVET may generate "added value" even outside of measures to promote geographical mobility. The initial spark for this came from the so-called 'second generation' of European projects, in which Member States were funded to test ECVET in their national contexts. The discussion paper also takes up findings, results and approaches from pilot initiatives like DECVET and JOBSTARTER CONNECT, and discusses barriers, options and scope for the use of unit-based concepts at the interfaces within the German (vocational) education system. (Autorenreferat, BIBB-Doku) – – 2008 verabschiedeten Europaïsches Parlament und Rat die 'Empfehlung zur Einrichtung eines europaïschen Leistungspunktesystems, ECVET'. Ziel des ECEVT ist es, Lernergebnisse, die in verschiedenen Bildungssystemen und in unterschiedlichen Kontexten der beruflichen Aus- und Fortbildung erbracht wurden, zu ub̈ertragen und wechselseitig anzuerkennen. In den vergangenen Jahren wurde eine Vielzahl von Schritten auf europaïscher Ebene und in den Mitgliedstaaten unternommen, um geeignete Rahmenbedingungen fur̈ eine ECVET-Anwendung zu schaffen. In vorliegendem Diskussionspapier wird die Frage aufgeworfen, inwieweit ECVET auch außerhalb von Mobilitaẗsmaßnahmen einen 'Mehrwert' erzielen kann. Die Initialzun̈dung hierfur̈ lieferte die sogenannte '2. Generation' von europaïsch gefor̈derten Projekten, die ECVET in ihren nationalen Kontexten erproben sollten. Das Diskussionspapier greift darub̈er hinaus auch Erfahrungen, Resultate und Ansaẗze aus Pilotinitiativen wie DECVET und JOBSTARTER CONNECT auf und thematisiert Hindernisse, Optionen und Spielraüme fur̈ den Einsatz von unit-basierten Konzepten an den Schnittstellen im deutschen (Berufs)Bildungssystem. (Hrsg., BIBB-Doku)
urn:nbn:de:0035-0510-8
Keywords: 370